The Diversity of Ecotourism Potentials in Kelimutu National Park of Ende Regency - Gadi Djou, Josef A.; Baiquni, M.; Widodo, Tri; Fandeli, C. (E-Journal of Tourism; Volume 3 Number 2 (September 2016)DO - 10.24922/eot.v3i2.24000, 2016)
Natural tourist destination management plays a crucial role in materializing three important aspects, namely conservation, participation, and education. As a tourist destination, Kelimutu National Park, possessing a big ecosystem potential, tourist and cultural potentials, is expected to provide economy, culture, and conservation impacts on the society surrounding Kelimutu National Park. The problem of this study is how the variety of ecotourism potential in Kelimutu National Park is able to prosper the surrounding society. To answer this question, the definition of ecotourism, national park, national park ecotourism, and ecotourism potential need to be understood. Several methods used in answering the problems of the study are finding out the location of Kelimutu National Park, collecting qualitative data by conducting library research and participatory observation. The results were conceptually described, supported by tables and pictures.
Keywords: natural tourist destination, tourism potential, ecotourism